PENGARUH FAKTOR SOSIAL EKONOMI TERHADAP PENGANGGURAN DI PROVINSI BALI - Ketut Ayu Pradnya Dewi; I Komang Gde Bendesa (Universitas Udayana, 2023)
One of the factors hindering the development of the country is the high unemployment rate. This research was conducted in Bali. The research theme is COVID-19 related to population, economic growth, education, and unemployment. The data collection method in this study was indifferent observation. Data are secondary data used in this study. Data source is from Badampsat Statistics of Bali Province. The purpose of this study is to partially and simultaneously determine the effects of COVID-19 on population, economic growth, education and unemployment in Bali over the period 2010-2021. The results of the analysis also show that population, economic growth, education and COVID-19 have had a significant effect on Bali's unemployment rate at the same time. In part, population has a positive and significant effect on Bali's unemployment rate. Economic growth and education had a negative and significant effect on unemployment in Bali, and COVID-19 had a significant effect on unemployment in Bali. Keyword: Population, Economic Growth, Education, Covid-19 and Unemployment.